SOME MODERN APPROACHES TO ENGINEERING EDUCATION - I. R. Agamirzian; E. A. Krouk; V. B. Prokhorova (Высшее образование в России)
This article discusses the demands that the digital economy and the modern labor market make on engineering education. The authors dwell on the issues of the formation of an educational space for training of engineers, the construction of an educational process on the basis of the project model of training. The question under consideration is whether the profession of an engineer is elite or mass. The paper proposes the classification of engineering labor depending on the nature of the work performed, presents new basic skills required for engineers to successfully enter the labor market in the digital economy. It is concluded that there is a need for a radical change in the educational process of engineer training, for attracting employers to the training process not only at the stage of students’ practical skills formation, but also at the stage of planning the educational process as a whole. The goal of these changes is, ultimately, reducing the time of specialists’ adaptation in workplace. This will enable the methods and technologies of the digital economy to be early implemented.